Impact of the Covid-19 Pandemic on the Occupational Roles of Private Security Officers in South Africa - Pillay, Kris (Southern African Journal of Security)
The World Health Organization (WHO) declared the coronavirus disease (Covid-19) a global pandemic on 11 March 2020. The rapid spread of the virus disrupted many aspects of society including the role of private security officers (PSOs). In South Africa, when the government declared a National State of Disaster to prevent the spread of the virus, the private security industry was considered an “essential service”. As the country’s lockdown measures came into effect, businesses sought the services of private security companies to ensure the safety and security of their clients and premises. Consequently, PSOs were caught off guard due to their inadequate preparedness and lack of proper training. The purpose of the current study was to examine how the Covid-19 pandemic impacted the occupational environment of PSOs in South Africa. There was a need for the study because the traditional roles of PSOs were disrupted by government lockdown regulations and there was a shortage of current and easily accessible information. Hence, the study applied the interpretive content analysis of literature harvested from different databases. The findings revealed that PSOs were obliged to take on additional roles and responsibilities for which they were not prepared, such as applying social distancing at business premises; enforcing restrictions on people not wearing masks; and screening people’s temperatures. Further, the findings revealed that PSOs had the right to refuse entry to people who did not abide by the rules, but they had less latitude to enforce the rules arbitrarily. The study recommends that the training requirements of PSOs be redesigned and modernised to meet the skills gap suited for a new generation of PSOs.